2016
DOI: 10.1080/17430437.2016.1173922
|View full text |Cite
|
Sign up to set email alerts
|

Improving the physical and mental well-being of typically hard-to-reach men: an investigation of the impact of the Active Rovers project

Abstract: Abstract:Strong associations exist between physical activity (PA) levels and incidence morbidity and mortality. Evidence suggests that PA levels decline with age but incidence of sedentary behaviour is high. This paper examines the effectiveness of a PA intervention hosted by a professional football club. It explores the impact of the intervention upon mental wellbeing, health perceptions, and lifestyle knowledge in men often classed as hard-to-reach (HTR).Data were collected through a shortened version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…It also became clear that, for many players, given a choice, they would not ordinarily be friends with each other but they felt bound together as a result of the unintended outcomes associated with their career. It has been argued that meaningful social relationships and affiliations are key determinants in positive engagements in both physical and mental health (Lewis et al, 2016). The data presented here, however, indicates that professional golfers struggled to strike up meaningful relationships with fellow players on tour, and came to feel dislocated given their 'real' group of friends and family were back at home.…”
Section: Loneliness Isolation and Work Life Balancecontrasting
confidence: 39%
“…It also became clear that, for many players, given a choice, they would not ordinarily be friends with each other but they felt bound together as a result of the unintended outcomes associated with their career. It has been argued that meaningful social relationships and affiliations are key determinants in positive engagements in both physical and mental health (Lewis et al, 2016). The data presented here, however, indicates that professional golfers struggled to strike up meaningful relationships with fellow players on tour, and came to feel dislocated given their 'real' group of friends and family were back at home.…”
Section: Loneliness Isolation and Work Life Balancecontrasting
confidence: 39%
“…Further, trusts have existing relationships with healthcare providers and in some cases long standing involvement in their local communities . Trusts also have access to facilities that can be used to promote PA within their local community, including club branded facilities (Lewis et al, 2017, Martin et al, 2016. Furthermore, recognizing that traditional healthcare settings can appear off-putting to some groups including adult men (Lewis et al, 2017, non-clinical settings have also been found to engage individuals in community football and PA programmes (White et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As with other football for mental health projects, the majority of participants were male (three were female), as football remains a contested site where gender relations continue to be reproduced, maintained and resisted [46]. More broadly, in this context, this could be partially viewed as a positive, as football projects can attract 'hard to reach' men who are known to under-use health services [36,47,48].…”
Section: Participantsmentioning
confidence: 98%
“…This is especially important to engage 'hard to reach' populations within a mental health context. Research suggests that men's reluctance to seek support can further exacerbate distress and can often lead to suicide [34], and initial studies have suggested that football can be useful to engage these often 'hard to reach' male demographics who are most at risk [35,36].…”
Section: Football Specific Projectsmentioning
confidence: 99%
See 1 more Smart Citation